Peningkatan Kesadaran Lingkungan Melalui Bank Sampah Digital di Kelurahan Panjang Jiwo Kota Surabaya - Ramadhan, Aldino; Lestari, Nabila Ayu (UNITY: Journal of Community Service, 2025)
Urban waste management remains a serious environmental issue in Indonesia, especially in Java island. Kelurahan Panjang Jiwo, Surabaya, faces excessive domestic waste production due to low public awareness and inadequate waste sorting systems. This community service initiative introduced a digital waste bank model aimed at improving environmental awareness and encouraging behavior change through technology. The program involved workshops, digital application training, clean-up actions, and follow-up evaluations. Results show improved sorting behavior, stronger community involvement, and increased interest in recycling activities. This project highlights the potential of digital tools to support environmental education and waste management at the local level.